THE EFFICIENCY OF MAGNETIC FIELD APPLICATION IN FERROMAGNETIC POWDER MILLING PROCESS - Y.M. VERNIGOROV; I.N. EGOROV; S.I. EGOROVA (Advanced Engineering Research)
The method of efficiency and quality increase of dry milling in impact mill by creating the magnetovibrating layer in rotating beater area is considered. It is shown that the milling degree and average particle size of produced powder depend not only of milling time, but also of magnetic field regimes.